DOI: 10.22215/etd/2017-12098
|View full text |Cite
|
Sign up to set email alerts
|

The Indirect Effect of Employee Entitlement: A Career Stage Perspective

Abstract: The moderating role of career stage on employee entitlement and the mediating role of organizational justice on the relationship between employee entitlement and outcomes of work engagement and counterproductive work behaviours were examined with a sample of 624 Canadian government and North America employees. Contrary to expectations, career stage did not significantly impact levels of employee entitlement. Likewise, full scale organizational justice was not found to be a significant mediator; however, some o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 96 publications
(156 reference statements)
0
1
0
Order By: Relevance
“…It is worth mentioning that employee entitlement in her research has been analyzed from the perspective of others, not from the perspective of a particular individual (self-reported). Lawlor (2017) assumed that there is no mediation effect of organizational justice on the relationship between employee entitlement and CWBs, but there is a significant mediation effect for the subscales of procedural and informational justice. In this particular case, the study was conducted using the self-reported scale of employee entitlement, although CWBs were not divided into behavior that may be directed towards the organization or coworkers.…”
Section: Employee Entitlement and Work Behaviormentioning
confidence: 99%
“…It is worth mentioning that employee entitlement in her research has been analyzed from the perspective of others, not from the perspective of a particular individual (self-reported). Lawlor (2017) assumed that there is no mediation effect of organizational justice on the relationship between employee entitlement and CWBs, but there is a significant mediation effect for the subscales of procedural and informational justice. In this particular case, the study was conducted using the self-reported scale of employee entitlement, although CWBs were not divided into behavior that may be directed towards the organization or coworkers.…”
Section: Employee Entitlement and Work Behaviormentioning
confidence: 99%